A Business Sustainability Model for Government Corporations. A Belgian Case Study. (1st July 2013) - Benijts, Tim
ABSTRACT A government's decision to tackle societal non‐sustainability problems by setting up a government corporation also necessitates the choice of a business model. This article seeks to contribute to this debate through an analysis of the (linkages between the key elements of the) business model of the Kringloopfonds (TKF), a Belgian government corporation set up in order to provide finance to sustainable companies. Based on documentary information and semi‐structured interviews with stakeholders TKF's business model is reconstructed which next is evaluated by means of program theory. It was found that TKF's portfolio allocation rule did not foresee in sufficient flexibility in order to cope with the shortage in financeable companies TKF was confronted with. This case thereby advocates for more business model flexibility in terms of portfolio allocation rules, time and asset requirements as well as for thorough sensitivity analyses testing business model's resistance to an initial and temporary shortage of sustainable companies.